KONSENTRASI HAMBAT MINIMUM (KHM) EKSTRAK DAUN TEH (Camellia sinensis L.) PADA Escherichia coli DAN Salmonella sp. - WIDIANA S.Si, M.Si, RINA (STKIP PGRI Sumatera Barat, 2012)
Diarrhea is the condition loosing too much liquid and electrolyte throughfeces and it is second biggest cause of infant death in Indonesia. Diarrhea iscaused by Salmonella sp and Escherichia coli bacteria. Inappropriate drug usedsuch as anti diarrhea and antibiotic can cause another health problem. Analternative treatment which does not cause side effect to the diarrhea victim isusing an anti microbe active of the plant medicine. One of the plant which is usedby the people as a treatment for the diarrhea victim is tea leaves (Camelliasinensis L.). it contains anti microbe active such as catecin, tannin, flavonoid andsaponin. Thus, the research was conducted to find out the minimum restrictionconcentrate of Camellia sinensis L. in E. coli and Salmonella sp.The minimum restriction concentration is used dilution method with jellyas the media (Jelly dilution method) by double it. The concentrations of E. coliare 50 %, 25 %, 12,5 %, 6,25 %, 3,125 % and 1,56 % with 10 % antibioticampicilin control. The concentrations for Salmonella sp are 50 %, 25 %, 12,5 %,6,25 %, 3,125 %, 1,56 %, 0,78 %, 0,39 %, 0,195 % and 0,0975 %. The data wasanalyzed in qualitative method by examining the minimum restriction of tealeaves extract (Camellia sinensis L.) in the bacteria that caused diarrhea. Theresearch was conducted on August 2010 in Biology Laboratory of STKIP PGRIWest Sumatera. Tea leaves was extracted in Chemical Laboratory of KopertisWilayah X Padang. The research found that E. coli is more resistant to tea leavesthan Salmonella sp. The minimum restriction concentrate of tea leaves extract(Camellia sinensis L.) in E. coli is 3,125% and 0,0975% in Salmonella sp.